Demographic disparities in the incidence and case fatality of subarachnoid haemorrhage: an 18-year nationwide study from New ZealandResearch in context - Ilari Rautalin; Rita V. Krishnamurthi; Craig S. Anderson; P. Alan Barber; Suzanne Barker-Collo; Derrick Bennett; Ronald Boet; Jason A. Correia; Jeroen Douwes; Andrew Law; Balakrishnan Nair; Amanda G. Thrift; et al. (Elsevier, 2024)
Summary: Background: Although the incidence and case-fatality of subarachnoid haemorrhage (SAH) vary within countries, few countries have reported nationwide rates, especially for multi-ethnic populations. We assessed the nationwide incidence and case-fatality of SAH in New Zealand (NZ) and explored variations by sex, district, ethnicity and time. Methods: We used administrative health data from the national hospital discharge and cause-of-death collections to identify hospitalised and fatal non-hospitalised aneurysmal SAHs in NZ between 2001 and 2018. For validation, we compared these administrative data to those of two prospective Auckland Regional Community Stroke Studies. We subsequently estimated the incidence and case-fatality of SAH and calculated adjusted rate ratios (RR) with 95% confidence intervals to assess differences between sub-populations. Findings: Over 78,187,500 cumulative person-years, we identified 5371 SAHs (95% sensitivity and 85% positive predictive values) resulting in an annual age-standardised nationwide incidence of 8.2/100,000. In total, 2452 (46%) patients died within 30 days after SAH. Compared to European/others, Māori had greater incidence (RR = 2.23 (2.08-2.39)) and case-fatality (RR = 1.14 (1.06-1.22)), whereas SAH incidence was also greater in Pacific peoples (RR = 1.40 (1.24-1.59)) but lesser in Asians (RR = 0.79 (0.71-0.89)). By domicile, age-standardised SAH incidence varied between 6.3-11.5/100,000 person-years and case fatality between 40 and 57%. Between 2001 and 2018, the SAH incidence of NZ decreased by 34% and the case fatality by 12%. Interpretation: Since the incidence and case-fatality of SAH varies considerably between regions and ethnic groups, caution is advised when generalising findings from focused geographical locations for public health planning, especially in multi-ethnic populations. Funding: NZ Health Research Council.